# Class 9 RD Sharma Solutions – Chapter 2 Exponents of Real Numbers- Exercise 2.2 | Set 2

**Question 12. Determine (8x)**^{x}, if 9^{x+2} = 240 + 9^{x}.

^{x}, if 9

^{x+2}= 240 + 9

^{x}.

**Solution:**

We have,

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.=> 9

^{x+2}= 240 + 9^{x}=> 9

^{x+2}− 9^{x}= 240=> 9

^{x}(9^{2 }− 1) = 240=> 9

^{x}= 240/80=> 3

^{2x}= 3=> 2x = 1

=> x = 1/2

Therefore, (8x)

^{x}= [8 × (1/2)]^{1/2}= 4

^{1/2}= 2

**Question 13. If 3**^{x+1} = 9^{x−2}, find the value of 2^{1+x}.

^{x+1}= 9

^{x−2}, find the value of 2

^{1+x}.

**Solution:**

We have,

=> 3

^{x+1}= 9^{x−2}=> 3

^{x+1}= (3^{2})^{x−2}=> 3

^{x+1}= 3^{2x−4}=> x + 1 = 2x − 4

=> x = 5

Therefore, 2

^{1+x}= 2^{1+5}= 2

^{6}= 64

**Question 14. If 3**^{4x }= (81)^{−1} and (10)^{1/y} = 0.0001, find the value of 2^{−x+4y}.

^{4x }= (81)

^{−1}and (10)

^{1/y}= 0.0001, find the value of 2

^{−x+4y}.

**Solution:**

We are given,

=> 3

^{4x}= (81)^{−1}=> 3

^{4x}= (3^{4})^{−1}=> 3

^{4x}= (3)^{−4}=> 4x = −4

=> x = −1

And also, (10)

^{1/y }= 0.0001=> (10)

^{1/y}= (10)^{−4}=> 1/y = −4

=> y = −1/4

Therefore, 2

^{−x+4y }= 2^{1+4(−1/4) }= 2

^{1−1 }= 1

**Question 15. If 5**^{3x} = 125 and 10^{y} = 0.001. Find x and y.

^{3x}= 125 and 10

^{y}= 0.001. Find x and y.

**Solution:**

We are given,

=> 5

^{3x}= 125=> 5

^{3x}= 5^{3}=> 3x = 3

=> x =1

Also, (10)

^{y}= 0.001=> 10

^{y}= 10^{−3}=> y = −3

Therefore, the value of x is 1 and the value of y is –3.

**Question 16. Solve the following equations:**

**(i) 3**^{x+1} = 27 × 3^{4}

^{x+1}= 27 × 3

^{4}

**Solution:**

We have,

=> 3

^{x+1}= 27 × 3^{4}=> 3

^{x+1}= 3^{3}× 3^{4}=> 3

^{x+1 }= 3^{7}=> x + 1 = 7

=> x = 6

**(ii) **** **

**Solution:**

We have,

=>

=>

=>

=>

=> 4x = −8/y = 3

=> x = 3/4 and y = −8/3

**(iii) 3**^{x−1} × 5^{2y−3} = 225

^{x−1}× 5

^{2y−3}= 225

**Solution:**

We have,

=> 3

^{x−1}× 5^{2y−3}= 225=> 3

^{x−1}× 5^{2y−3}= 3^{2}× 5^{2}=> x − 1 = 2 and 2y − 3 = 2

=> x = 3 and 2y = 5

=> x = 3 and y = 5/2

**(iv) 8**^{x+1} = 16^{y+2} and (1/2)^{3+x} = (1/4)^{3y}

^{x+1}= 16

^{y+2}and (1/2)

^{3+x}= (1/4)

^{3y}

**Solution:**

We have,

=> 8

^{x+1}= 16^{y+2}=> (2

^{3})^{x+1}= (2^{4})^{y+2}=> 2

^{3x+3}= 2^{4y+8}=> 3x + 3 = 4y + 8 . . . . (1)

Also, (1/2)

^{3+x}= (1/4)^{3y}=> (1/2)

^{3+x}= [(1/2)^{2}]^{3y}=> (1/2)

^{3+x}= (1/2)^{6y}=> 3 + x = 6y

=> x = 6y − 3 . . . . (2)

Putting (2) in (1), we get,

=> 3(6y − 3) + 3 = 4y + 8

=> 18y − 9 + 3 = 4y + 8

=> 14y = 14

=> y = 1

Putting y = 1 in (2), we get,

x = 6(1) − 3 = 6 − 3 = 3

Therefore, the value of x is 1 and the value of y is –3.

**(v) 4**^{x−1} × (0.5)^{3−2x} = (1/8)^{x}

^{x−1}× (0.5)

^{3−2x}= (1/8)

^{x}

**Solution:**

We have,

=> 4

^{x−1}× (0.5)^{3−2x}= (1/8)^{x}=> (2

^{2})^{x−1 }× (1/2)^{3−2x}= [(1/2)^{3}]^{x}=> 2

^{2x−2}× 2^{2x−3}= 2^{−3x}=> 2

^{2x−2+2x−3}= 2^{−3x}=> 2

^{4x−5}= 2^{−3x}=> 4x − 5 = −3x

=> 7x = 5

=> x = 5/7

**(vi) **** **

**Solution:**

We have,

=>

=>

=> 1/2 = 2x − 1

=> 2x = 3/2

=> x = 3/4

**Question: 17. If a and b are distinct positive primes such that, **** find x and y.**

**Solution:**

We have,

=>

=> (a

^{6 }b^{−4})^{1/3}= a^{x}b^{2y}=> a

^{6/3 }b^{−4/3}= a^{x}b^{2y}=> a

^{2 }b^{−4/3}= a^{x}b^{2y}=> x = 2 and 2y = −4/3

=> x = 2 and y = −2/3

**Question 18. If a and b are different positive primes such that,**

**(i) ****, find x and y.**

**Solution:**

We have,

=>

=> (a

^{−1−2 }b^{2+4})^{7}÷ (a^{3+2 }b^{−5−3}) = a^{x}b^{y}=> (a

^{−3 }b^{6})^{7}÷ (a^{5 }b^{−8}) = a^{x}b^{y}=> (a

^{−21 }b^{42}) ÷ (a^{5 }b^{−8}) = a^{x}b^{y}=> (a

^{−21−5 }b^{42+8}) = a^{x}b^{y}=> (a

^{−26 }b^{50}) = a^{x}b^{y}=> x = −26, y = 50

**(ii) (a + b)**^{−1}(a^{−1} + b^{−1}) = a^{x}b^{y}, find x+y+2.

^{−1}(a

^{−1}+ b

^{−1}) = a

^{x}b

^{y}, find x+y+2.

**Solution:**

We have,

=> (a + b)

^{−1}(a^{−1}+ b^{−1}) = a^{x}b^{y}=> = a

^{x}b^{y}=> = a

^{x}b^{y}=> 1/ab = a

^{x}b^{y}=> a

^{−1}b^{−1 }= a^{x}b^{y}=> x = −1 and y = −1

So, x+y+2 = −1−1+2 = 0.

**Question 19. If 2**^{x} × 3^{y} × 5^{z} = 2160, find x, y and z. Hence compute the value of 3^{x} × 2^{−y} × 5^{−z}.

^{x}× 3

^{y}× 5

^{z}= 2160, find x, y and z. Hence compute the value of 3

^{x}× 2

^{−y}× 5

^{−z}.

**Solution:**

We are given,

=> 2

^{x}× 3^{y }× 5^{z}= 2160=> 2

^{x }× 3^{y}× 5^{z}= 2^{4 }× 3^{3 }× 5^{1}=> x = 4, y = 3, z = 1

Therefore, 3

^{x}× 2^{−y}× 5^{−z}= 3^{4}× 2^{−3}× 5^{−1}= (81) (1/8) (1/5)

= 81/40

**Question 20. If 1176 = 2**^{a} × 3^{b} × 7^{c}, find the values of a, b and c. Hence, compute the value of 2^{a} × 3^{b} × 7^{-c} as a fraction.

^{a}× 3

^{b}× 7

^{c}, find the values of a, b and c. Hence, compute the value of 2

^{a}× 3

^{b}× 7

^{-c}as a fraction.

**Solution:**

We are given,

=> 1176 = 2

^{a}× 3^{b}× 7^{c}=> 2

^{3}× 3^{1}× 7^{2 }= 2a × 3b × 7c=> a = 3, b = 1, c = 2

Therefore, 2

^{a}× 3^{b}× 7^{−c}= 2^{3}× 3^{1}× 7^{−2}= (8) (3) (1/49)

= 24/49

**Question 21. Simplify**

**(i) **

**Solution:**

We have,

=

= (x

^{a+b−c})^{a−b }(x^{b+c−a})^{b−c }(x^{c+a−b})^{c−a}=

=

= x

^{0}= 1

**(ii) **

**Solution:**

We have,

=>

=>

=>

=>

=>

=>

=> x

^{0}= 1

**Question 22. Show that ****.**

**Solution:**

We have,

L.H.S. =

=

=

=

= R.H.S.

Hence proved.

**Question 23. (i) If a = x**^{m+n}y^{l}, b = x^{n+l}y^{m} and c = x^{l+m}y^{n}, prove that a^{m−n }b^{n−l }c^{l−m} = 1.

^{m+n}y

^{l}, b = x

^{n+l}y

^{m}and c = x

^{l+m}y

^{n}, prove that a

^{m−n }b

^{n−l }c

^{l−m}= 1.

**Solution:**

Given, a = x

^{m+n}y^{l}, b = x^{n+l}y^{m}and c = x^{l+m}y^{n}.We have,

L.H.S. = a

^{m−n}b^{n−l}c^{l−m}= (x

^{m+n}y^{l})^{m−n}(x^{n+l}y^{m})^{n−l}(x^{l+m}y^{n})^{l−m}=

=

= x

^{0}y^{0}= 1

= R.H.S.

Hence proved.

**(ii) If x = a**^{m+n}, y = a^{n+l }and z = a^{l+m}, prove that x^{m}y^{n}z^{l} = x^{n}y^{l}z^{m}.

^{m+n}, y = a

^{n+l }and z = a

^{l+m}, prove that x

^{m}y

^{n}z

^{l}= x

^{n}y

^{l}z

^{m}.

**Solution:**

Given, x = a

^{m+n}, y = a^{n+l}and z = a^{l+m}.We have,

L.H.S. = x

^{m}y^{n}z^{l}= (a

^{m+n})^{m }(a^{n+l})^{n}(a^{l+m})^{l}=

=

= (a

^{m+n})^{n}(a^{n+l})^{l}(a^{l+m})^{m}= x

^{n}y^{l}z^{m}= R.H.S.

Hence proved.